Factors In Implementing Early Initiation Of Breastfeeding at The Permata Hati Duri Hospital (HEALTH CARE: JURNAL KESEHATAN, 2026)
Early initiation of breastfeeding (IMD) is a crucial practice in newborn care that significantly influences the success of exclusive breastfeeding. Infants who do not receive IMD are at an increased risk of neonatal morbidity and mortality. This study aimed to identify the factors that influence the implementation of IMD at Permata Hati Duri Hospital in 2024. Using a quantitative method with a cross-sectional design, the study involved a population of 78 mothers in labor, selected through total sampling. Data collection was conducted using a questionnaire, and the analysis was performed both univariately and bivariately using the Gamma test, with a significance level of α = 0.05. The results of the statistical analysis revealed a significant impact of education level (p = 0.001), family support (p = 0.000), and maternal motivation (p = 0.000) on the approval of IMD implementation. Empirical findings showed that, although most mothers had a high educational background and good intrinsic motivation, many reported receiving very little support from their families. This lack of support is strongly associated with a high rate of maternal rejection or disagreement with early breastfeeding initiation (IMD), which reached 59%. In conclusion, the absence of external support from family members is a critical factor that can undermine a mother's clinical judgment, thereby hindering the implementation of early breastfeeding practices within the first hour postpartum, regardless of the mother's internal readiness.